2019
DOI: 10.3906/sag-1809-165
|View full text |Cite
|
Sign up to set email alerts
|

Does chest compression during cardiopulmonary resuscitation provide sufficient cerebral oxygenation?

Abstract: Background/aim: Some of the patients suffering from cardiac arrest (CA) remain in a chronic unconscious state in intensive care units (ICUs). The primary aim of this study was to evaluate the efficacy of chest compression (CC) on cerebral oxygenation during cardiopulmonary resuscitation (CPR). As a secondary goal, we attempted to determine the effects of regional cerebral oxygen saturation (rSO 2) values on consciousness and the survival rate using the Full Outline of Unresponsiveness (FOUR) scoring method. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“… 75 There was a wide overlap of mean or median cerebral oxygen saturation values between patients with and without ROSC, and this was also reflected in the cohort studies. 77 , 78 , 79 Only 1 observational study 80 compared the rates of ROSC with and without NIRS monitoring and found no difference between the groups. All other studies compared NIRS values in patients who achieved ROSC with those without ROSC.…”
Section: Physiological Monitoring During Cprmentioning
confidence: 99%
“… 75 There was a wide overlap of mean or median cerebral oxygen saturation values between patients with and without ROSC, and this was also reflected in the cohort studies. 77 , 78 , 79 Only 1 observational study 80 compared the rates of ROSC with and without NIRS monitoring and found no difference between the groups. All other studies compared NIRS values in patients who achieved ROSC with those without ROSC.…”
Section: Physiological Monitoring During Cprmentioning
confidence: 99%
“…90,91 There was no consensus on the predictive threshold value of rSco 2 for any outcomes. [92][93][94] A trend of rising rSco 2 (between 7% and 15% from baseline measurement) may be a more reliable predictive factor for ROSC. 90,95,96 The ScopRev also identified 2 observational studies of NIRS in children during CPR.…”
Section: Summary Of Evidencementioning
confidence: 99%
“… 90 , 91 There was no consensus on the predictive threshold value of rS O 2 for any outcomes. 92 , 93 , 94 A trend of rising rS O 2 (between 7% and 15% from baseline measurement) may be a more reliable predictive factor for ROSC. 90 , 95 , 96 …”
Section: Pals: Physiological Monitoring During Arrest To Guide Therapmentioning
confidence: 99%